Synchronizing Nitrogen Fertilization and Planting Date to Improve Resource Use Efficiency, Productivity, and Profitability of Upland Rice - Hussain, Tajamul; Gollany, Hero T.; Hussain, Nurda; Ahmed, Mukhtar; Tahir, Muhammad; Duangpan, Saowapa (Frontiers in Plant Science, 2022)
Synchronizing nitrogen (N) fertilization with planting date (PD) could enhance resource use efficiency and profitability of upland rice (Oryza sativa L.) production in Thailand. The objective of the study was to assess the upland rice responses to four N fertilization rates (NFR) and three planting dates. Field experiments were conducted during two growing seasons under four NFR: no N applied (N0), 30 (N30), 60 (N60) and 90 kg N ha–1 (N90) and NFR were applied at tillering and panicle emergence stages. The planting dates selected were early (PD1), intermedium (PD2), and late planting (PD3) between September to December of each season. The NFR and planting dates had a significant influence on the N uptake, N use efficiency (NUE), crop water productivity, yield and yield attributes, and profitability of upland rice production. A linear relationship among NFR, agronomic traits of upland rice, N uptake and crop water productivity was observed, and a significant seasonal effect was indicated. Fertilization at N90 under PD2 enhanced yields, yield attributes and grain yields, as well as crop water productivity by 56% and 105% during the second and first seasons, respectively. Grain N, total N, and straw N were increased by 159%, 159%, and 160%, and by 90%, 114%, and 153%, during the first and the second season, respectively. Enhanced N efficiencies including agronomic efficiency, recovery efficiency, partial factor productivity, and N harvest index at varying NFR observed under PD2 during both seasons. Highly significant (p<0.001) and positive associations were observed between agronomic attributes, N uptake, NUE and crop water productivity of upland rice in correlation assessment. Profitability from grain yields was observed with N fertilization and N90 resulted in maximum profit under all PD. Though, the highest marginal benefit–cost ratio was observed at N60 under PD2 during both seasons. Results suggest that NFR of 90 kg N ha–1, and planting at the end of September or start of October would enhance resource use efficiency, productivity, and maximize profitability. Furthermore, long–term field investigations with a range of NFR and adopting forecasting measures to adjust the planting date for upland rice are recommended.